DNA damage and antioxidant capacity in COPD patients with and without lung cancer - dos Santos, Camila Freitas; Braz, Mariana Gobbo [UNESP]; de Arruda, Nayara Micarelli [UNESP]; Caram, Laura [UNESP]; Nogueira, Duelene Ludimila [UNESP]; Tanni, Suzana Erico [UNESP]; de Godoy, Irma [UNESP]; Ferrari, Renata [UNESP] (Public Library of Science (PLoS), 2022)
Background and objective Chronic obstructive pulmonary disease (COPD) is characterized by chronic inflammation of the lower airways, and COPD patients show two to five times higher risk of lung cancer than smokers with normal lung function. COPD is associated with increased oxidative stress, which may cause DNA damage and lung carcinogenesis. Our aim was to evaluate DNA damage and oxidative stress (lipid peroxidation and antioxidant status) and their relationship in patients with COPD with and without lung cancer. Methods We evaluated 18 patients with COPD, 18 with COPD with lung cancer, and 18 controls (former or current smokers). DNA damage was evaluated in peripheral blood lymphocytes using a comet assay; the concentration of malondialdehyde (MDA) and hydrophilic antioxidant performance (HAP) were measured in the plasma. Results DNA damage was higher in patients with COPD with cancer than in the controls (p = 0.003). HAP was significantly lower in patients with COPD with cancer than in those without cancer and controls. The presence of lung cancer and COPD showed a positive association with DNA strand breaks and the concentration of MDA. Conclusion COPD with lung cancer was associated with elevated DNA damage in peripheral lymphocytes, and cancer and COPD showed a positive correlation with DNA damage. The antioxidant capacity showed a negative association with the interaction COPD and cancer and presence of COPD. The mechanisms underlying the increased incidence of lung cancer in COPD are unknown; DNA damage may be involved. Further research may provide insights into their development and treatment.